Role of Cinematography in Anticorruption Enlightenment: Global Experience - A. L. Melnikova; A. S. Mitsul (Russian Journal of Economics and Law)
Objective: to conduct a comprehensive interdisciplinary legal study of the role of cinematography in anti-corruption enlightenment of citizens.Methods: a structural and functional approach to the interpretation of society as a connection of subsystems, in which cinematography is a part of the cultural subsystem, while anti-corruption policy refers simultaneously to the public subsystem (enlightenment) and the state subsystem (politics). The chosen approach determines a set of specific research methods, such as a critical analysis of theoretical literature on corruption behavior and on the relationship between a viewer and a cinematography product in conjunction with an empirical study of various cases in the form of films and film projects devoted to anti-corruption topics.Results: the analysis of the mechanisms of building the relationships between a viewer and cinematography allowed identifying the possibilities of cinematography to have a long-term impact on a viewer, due not only to the technical capabilities of cinematography, but also to the psychobiological mechanisms of man. By the example of specific projects, the expediency of using cinema as an anti-corruption enlightenment tool was proved and justified. In particular, if the relevant messages are laid in the plot of a feature film, then, thanks to mirror neurons and human thinking mechanisms, they can serve educational purposes and demonstrate the consequences of corrupt behavior. It is important not to intimidate the audience with the horrors of living with corruption, but to show a positive way out and scenarios of living without it. This can lead to an increase in civic engagement, to an increase in interest in the issue under discussion, as well as to an increase in ratings of trust in the state.Scientific novelty: the article proves the inexpediency of evaluating cinema solely as a form of entertainment, and for the first time examines examples of the practical application of cinema for anti-corruption policy and enlightenment by comparing approaches used in different countries.Practical significance: the main conclusions of the article can be used in scientific, pedagogical and practical activities when developing long-term strategies and programs of anti-corruption enlightenment, as well as in the framework of cinematographic activities to assess the long-term consequences of the demonstrated film narrative.